Understanding the needs of local involvement in ensuring the sustainability of recreational forest landscape development - Hussein, Mohd Kher; Mohd Yunos, Mohd Yazid (Faculty of Design & Architecture, Universiti Putra Malaysia, 2015)
Local involvement in recreational forest landscape development process is very important to be focused on by the management. It can help in avoiding injustice in decision making. An effect of local involvement is necessary to ensure the sustainability of recreational forest. By involving them in the system, they can understand the rationale behind the planning decisions that have been, are and will be implemented. However, it was believed that local involvement in recreational forest landscape development is still at the unacceptable levels and needs improvement. Therefore, the aim of this study is to understand the locals’ needs in recreational forest landscape development process. The objective of the study is to explore and analyse people perception towards local involvement in recreational forest landscape development process in selected recreational sites, namely Sungai Chongkak Recreational Forest, Templer Recreational Forest and Sungai Tekala Recreational Forest, located in Selangor, Malaysia. Questionnaire survey has been conducted on a total of 533 participants. Results indicate that the present recreational forest landscape development of study sites will need to improve local involvement and improve their strategy in developing the site for sustainability in the future. The management should realize that locals’ involvement is necessary in order to offer a high satisfaction and fulfil local desires as well as to get full support from them. As a result, this could lead towards local economic benefits, active citizenship, and raised awareness of the locals’ and long‐term sustainability of ecological and aesthetic values.